Exceptionally long‐term persistence of DNA adducts formed by carcinogenic aristolochic acid I in renal tissue from patients with aristolochic acid nephropathy. Issue 2 (14th January 2014) - Schmeiser, Heinz H.; Nortier, Joëlle L.; Singh, Rajinder; Gamboa da Costa, Gonçalo; Sennesael, Jacques; Cassuto‐Viguier, Elisabeth; Ambrosetti, Damien; Rorive, Sandrine; Pozdzik, Agnieszka; Phillips, David H.; Stiborova, Marie; Arlt, Volker M.
<x xml:space="preserve">Abstract</x> Aristolochic acid (AA) causes aristolochic acid nephropathy (AAN), first described in women in Belgium accidently prescribed Aristolochia fangchi in a slimming treatment, and also Balkan endemic nephropathy (BEN), through probable dietary contamination with Aristolochia clematitis seeds. Both nephropathies have a high risk of urothelial cancer, with AA being the causative agent. In tissues of AAN and BEN patients, a distinct DNA adduct, 7‐(deoxyadenosin‐N6‐yl)‐aristolactam I (dA‐AAI), has been detected. DNA adducts can be removed through DNA repair, they can result in mutations through erroneous DNA replication or they can cause cell death. The dA‐AAI adduct induces AT to TA transversions in the tumor‐suppressor TP53 gene in experimental systems, matching TP53 mutations observed in urothelial tumors from AAN cancer cases. Using thin‐layer chromatography 32P‐postlabeling and mass spectrometric analysis we report the detection of dA‐AAI in renal DNA from 11 Belgian AAN patients over 20 years after exposure to AA had ceased. Our results showed that dA‐AAI is an established biomarker of AA exposure, and that this biomarker can be demonstrated to be persistent decades after a distinct AA exposure. Further, the persistence of dA‐AAI adducts appears to be a critical determinant for the AA mutational fingerprint frequently found in oncogenes and tumor suppressor genes recently identified by whole genome sequencing of AA‐associated urothelial tumors. The potential for exposure to AA worldwide is high; the unprecedented long‐term persistence of dA‐AAI provides a useful long‐term biomarker of exposure and attests to the role of AA in human urothelial malignancy.